Role of an Organic Intellectual for Counterculture Hegemony in Ambika Dutta Vyasa’s Shivraj Vijaya - Paudel, Yog Raj (The Outlook: Journal of English Studies, 2026)
This research explores the role of an organic intellectual in establishing counterculture hegemony in Ambika Dutta Vyasa’s novel Shivaraj Vijaya. It examines the ways invaders suppress native people and how the natives resist the suppression. It is an analysis of counterculture hegemony through a close reading of selected primary and secondary texts from postcolonial perspectives. Deductive reasoning, retrospective and introspective methods were followed in analysis.  Antonio Gramsci’s concept of cultural hegemony and subaltern consciousness of cultural domination and construction of cultural space for resistance, and Michael Foucault’s concept of power and resistance as interconnected forces are used as theoretical perspectives to explore how colonialism as a cultural activity establishes hegemony and how the natives resist it to establish counterculture hegemony. It is found that Shivaraj, the protagonist of the novel, plays the role of an organic intellectual against the invaders and succeeds in establishing counterculture hegemony. He applies a strategy of making people aware of cultural control and enabling them to realize differences in social, religious and cultural freedom they experienced before and after the invaders’ domination.  The hegemonized rule is juxtaposed by Shivaji’s resolution for resistance, warring strategies, constructive and caring approaches to people, which motivate the natives to resist invaders. The finding has established a perspective that a leader with resolute and sincere actions can become a reviving energy of culturally dominated people to support the leadership, and establish counterculture hegemony. This finding will be helpful in analyzing any text with cultural clashes and counter hegemony practices.